ANALISIS SISTEM INFORMASI PENERIMAAN DANPENGELUARAN KAS UNTUK MENINGKATKAN PENGENDALIAN INTERNAL PADA PT. SOCFIN INDONESIA KEBUN MATAPAO KECAMATAN TELUK MENGKUDU KABUPATEN SERDANG BEDAGAI - Fahma, Jerniati; Wirananda, Henny Andriyani (Al-Buhuts, 2023)
The accounting information system is one of the means for management in carrying out internal controls related to cash receipts and disbursements so that the implementation can run according to the plans and objectives that have been set. The purpose of this study was to determine the internal control of cash and accounting information systems used in controlling the company's cash. The method used in this study is a qualitative description method. The results of this study indicate that the information system of PT. Socfin Indonesia Kebun Mata Pao for receipts and disbursements of cash already meets the elements of internal control.